1992
DOI: 10.3181/00379727-199-43358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia on Megakaryocyte Size and Number of C3H and BALB/c Mice

Abstract: In an effort to explain the different platelet production capabilities of both normal and hypoxic male and female C3H and BALB/c mice, megakaryocyte size and number were determined utilizing bone marrow from both normal and hypoxic mice. The results indicate that normal BALB/c female mice have increased numbers of megakaryocytes, but of smaller size compared with either BALB/c male mice or to both sexes of C3H mice. An inverse relationship between the size and number of megakaryocytes was found in both normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…3) We suspect that impaired TPO production is not a pathogenic component of this disorder, because McDonald and coworkers reported that, in mice, hypoxia does not reduce TPO production. 20 One treatment option for neonates with the thrombocytopenia of perinatal asphyxia is PLT transfusion, but much investigation is needed to determine the risks and benefits of transfusions for neonates with this condition and to establish transfusion guidelines for this group. As highlighted by Josephson and colleagues 2 in a recent symposium, PLT transfusion strategies for neonates currently lack a strong evidence base, yet this is needed as a high priority.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3) We suspect that impaired TPO production is not a pathogenic component of this disorder, because McDonald and coworkers reported that, in mice, hypoxia does not reduce TPO production. 20 One treatment option for neonates with the thrombocytopenia of perinatal asphyxia is PLT transfusion, but much investigation is needed to determine the risks and benefits of transfusions for neonates with this condition and to establish transfusion guidelines for this group. As highlighted by Josephson and colleagues 2 in a recent symposium, PLT transfusion strategies for neonates currently lack a strong evidence base, yet this is needed as a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms resulting in the thrombocytopenia of perinatal asphyxia are obscure, but several experiments have generated potential explanations. For instance, McDonald and colleagues subjected adult mice to hypoxia and found a decrease in the size of individual megakaryocytes in the marrow and an overall reduction in marrow megakaryocyte mass, suggesting that the primary kinetic mechanism was reduced PLT production. Saxonhouse and coworkers evaluated whether megakaryocyte progenitors are damaged directly by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that fetal hypoxia is causally involved in both varieties, which is consistent with the studies of McDonald et al . in t adult mice subjected to hypoxia [26], and marrow culture studies of Saxonhouse et al [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia in adult mice causes a decrease in the size and production of the megakaryocytes in the bone marrow [76]. Although the megakaryocytes appear to not be injured by hypoxia, the cells in the bone marrow surrounding them are affected and decrease the release of platelet promoting factors [77].…”
Section: Thrombocytopeniamentioning
confidence: 99%